EPR studies on Na-oleate coated Fe3O4 nanoparticles - Köseoğlu, Yúksel; Yıldız, Fikret; Kim, Dokyung; Muhammed, Mamoun A.; Aktaş, Bekir (My University, 2004)
Superparamagnetic iron oxide nanoparticles were prepared by the co-precipitation technique. Then, fine iron oxide nanoparticles were coated by Na-oleate. Magnetic properties of Na-oleate coated and uncoated iron oxide nanoparticles were investigated by Electron Paramagnetic Resonance (EPR) technique. At room temperature, a single, strong and broad EPR signal was observed for both samples with effective g-values of 2,0839 and 2,18838 for coated and uncoated samples, respectively. The intensity, line width and the resonance field for both coated and uncoated samples are strongly temperature dependent. When the sample is coated with Na-oleate, the line width and the resonance field values of the EPR signal increase due to the decrease in the magnetic interaction between the particles. The total effective magnetic moment of such coated particles is found to decrease, which is most likely due to a non-collinear spin structure originated from the pinning of the surface spins and coated surfactant at the interface of nanoparticles. © 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. © 2008 Elsevier B.V., All rights reserved.
Keywords: Electron tunneling; Iron; Magnetic moments; Magnetic resonance imaging; Magnetization; Paramagnetic resonance; Signal processing; Surface active agents; Transmission electron microscopy; X ray powder diffraction; Bulk solids; Ferrofluids; Magnetic interactions; Quantum dimensions; Nanostructured materials